Kapitalisme Dan Islam Dalam Pergulatan Ekonomi - Yoyok Rimbawan (Sekolah Tinggi Agama Islam At-Tahdzib, Ngoro, Jombang, Indonesia, 2019)
The unpreparedness of human resources in the development of the state, especially the economy, has resulted in the choice of many Islamic countries being oriented and oriented towards these two main ideologies, namely the capitalist model developed by Western countries or the socialists adopted by Russia and China. As well as adopting the totality of these two ideologies as a foothold in managing human resources, natural resources in economic activities. Although both of them have principles that are not in accordance with Islamic teachings.